2015
DOI: 10.1093/mnrasl/slv056
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate inclinations of type 2 Coronal-Line Forest AGN

Abstract: Coronal-Line Forest Active Galactic Nuclei (CLiF AGN) are remarkable in the sense that they have a rich spectrum of dozens of coronal emission lines (e.g. [FeVII], [FeX] and [NeV]) in their spectra. Rose, Elvis & Tadhunter (2015) suggest that the inner obscuring torus wall is the most likely location of the coronal line region in CLiF AGN, and the unusual strength of the forbidden high ionization lines is due to a specific AGN-torus inclination angle. Here we test this suggestion using mid-IR colours

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…Among more face-on galaxies (b/a < 0.6), we do not always detect H i; when we detect H i the absorption lines can have lower column densities than in edgeon sources. When a source is 4.6 µm bright, the WISE colours (W2-W4) allow us to estimate the orientation of the circumnuclear dust with respect to the AGN (Crenshaw et al 2000;Fischer et al 2014;Rose et al 2015). Among the 42 4.6 µm bright sources of our sample, 28 have W2-W4< 6, which suggests an unobscured AGN, i.e.…”
Section: Dmentioning
confidence: 96%
“…Among more face-on galaxies (b/a < 0.6), we do not always detect H i; when we detect H i the absorption lines can have lower column densities than in edgeon sources. When a source is 4.6 µm bright, the WISE colours (W2-W4) allow us to estimate the orientation of the circumnuclear dust with respect to the AGN (Crenshaw et al 2000;Fischer et al 2014;Rose et al 2015). Among the 42 4.6 µm bright sources of our sample, 28 have W2-W4< 6, which suggests an unobscured AGN, i.e.…”
Section: Dmentioning
confidence: 96%
“…Rose et al (2015a) argue that even in the classical unification model with a toroidal obscuring region, a small fraction of viewing directions might result in both strong coronal lines and obscured broad-line region (another such example from the Reyes et al 2008 sample is analyzed by Villar-Martín et al 2011). This picture is consistent with the distribution of dust temperatures in these objects and in type 2 quasars, in that coronal-line AGNs are warmer as inferred from the infrared colors than are other type 2 quasars.…”
Section: [O Iii] Properties and Bolometric Luminositymentioning
confidence: 99%
“…The computed inclinations of the type 1 AGNs studied in Fischer et al (2013) are clearly pole-on (á ñ = + -i 15 5 degrees) when compared to type 2 AGNs (á ñ = + -i 63 4 degrees). Interestingly, there is a lack of AGNs with inclinations that are intermediate between these distributions (Rose et al 2015b). Using WISE (W2-W4) colors as a proxy for the AGN inclination, Rose et al (2015b) showed that type 2 CLiF AGNs seem to have inclinations which are intermediate between typical type 1 and 2 AGNs.…”
Section: Clif Inclination Anglesmentioning
confidence: 99%
“…To support this, RET15 showed that the coronal line emitting region lies at a distance approximately equal to the dust sublimation radius, that is, the boundary of the inner torus wall (Suganuma et al 2006). Rose et al (2015b) employed the Fischer et al (2014) relation between inclination angle and mid-IR color to show that type 2 CLiF AGNs lie at angles intermediate between type 1 and type 2 AGNs.…”
Section: Introductionmentioning
confidence: 99%